Ultrasound-Guided Diffuse Optical Tomography for Predicting and Monitoring Neoadjuvant Chemotherapy of Breast Cancers: Recent Progress. (January 2016) - Xu, Chen; Vavadi, Hamed; Merkulov, Alex; Li, Hai; Erfanzadeh, Mohsen; Mostafa, Atahar; Gong, Yanping; Salehi, Hassan; Tannenbaum, Susan; Zhu, Quing
In this manuscript, we review the current progress of utilizing ultrasound-guided diffuse optical tomography (US-guided DOT) for predicting and monitoring neoadjuvant chemotherapy (NAC) outcomes of breast cancer patients. We also report the recent advance on optical tomography systems toward portable and robust clinical use at multiple clinical sites. The first patient who has been closely monitored before NAC, at day 2, day 8, end of first three cycles of NAC, and before surgery is given as an example to demonstrate the potential of US-guided DOT technique.